Hasil Tangkapan Mini Pure Seine Di Perairan Teluk Ambon Luar Dan Selatan Pulau Ambon - Jacobus Bunga Paillin; Friesland Tuapetel; Stany R. Siahainenia (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2023)
A purse seine is an active fishing gear used by fishermen in Ambon Island to catch small pelagic fish that gather in high abundance, although the information is still limited. The purpose of this research is to determine the species composition and size distribution of the catch from the mini purse seine in the waters of Outer Ambon Bay (TAL) and South Ambon Island (SPA). From the results of this research, there are four types in TAL waters and two types in SPA. In TAL, the captured fish species were Decapterus sp (Scad), Selar sp (Selar), Sardinella sp (Sardine), and Rastreliger sp (Mackerel). Sardine had the highest catch percentage at 28.41%, followed by scad (25.28%), mackerel (23.27%), and selar (23.04%). In the SPA waters, only scad (Decapterus sp) and selar (Selar sp) were found, with catch percentages of 57.83% and 42.17%, respectively. The average size distribution of scad caught with the mini purse seine in TAL waters was 16.62 cm, selar (17.22 cm), sardine (13.36 cm), and mackerel (17.34 cm). In SPA waters, the average size distribution of scad was 17.59 cm, and selar (16.63 cm).